OFR-146-81 Massive Sulfide Tailing Disposal Using The Thickened Discharge Method - 1.1.0 The Crandon Ore Body - Introduction - 1.1.1 Discovery - Gerald M. Bandholz (The National Institute for Occupational Safety and Health (NIOSH), 1981)
Exxon Minerals Company, a division of Exxon Corporation, has been exploring for base metal deposits in the Precambrian volcanic rocks in northern Wisconsin since 1970. Aerial electromagnetic surveys of the area, conducted in 1974, reported an anomaly, near Crandon, in Forest County. In the summer of 1975, the first diamond drill entered the anomaly, representing the 25th prospect Exxon had drilled in Wisconsin. This first hole revealed significant mineralization containing zinc and copper. Subsequent drilling confirmed the discovery of a sizeable zinc-copper massive sulfide are body. 1.1.2 Location The deposit is located in northeastern Wisconsin within a topographical high called the Northern Highlands region. The deposit lies about 5 miles directly south of Crandon and about 2 miles east of State Highway 55 on Sand Lake Road (see fig. 1). Other local communities include Rhinelander 28 miles west, Antigo 45 miles south, and Iron River and Iron Mountain, in Michigan, 75 and 44 miles east and north of Crandon respectively. In relation to the lakes and streams, the deposit lies 0.25 miles north of Little Sand Lake, and about 1 mile south of Swamp Creek.